Eltrombopag in Good’s Syndrome - Håvard Anton Kristiansen; Signe Spetalen; Yngvar Fløisand; Dag Heldal (Case Reports in Hematology)
Good’s syndrome is a rare acquired immunodeficiency associated with thymoma. Eltrombopag is a thrombopoietin receptor agonist and has been shown to be a valuable supplement to the treatment of several types of refractory cytopenias. In this paper, we describe a male patient suffering from Good’s syndrome with immune-mediated T-cell driven pancytopenia and absence of megakaryopoiesis. He was successfully treated with eltrombopag resulting in a multilineage clinical response.